Analysis of the Perceptions Shared by Young People about the Relevance and Versatility of Religion in Culturally Diverse Contexts - Sonia García-Segura; María-José Ma; Carmen Gil-Pino (MDPI AG, 2022)
This paper analyses the relevance of religion for adolescents in the realm of peer relationships, both within and outside of educational institutions. The sample consisted of 385 young individuals attending different Secondary Education institutions located in a Spanish province characterized by its cultural diversity. The tool used to collect the information was the REDCo questionnaire. The results of the data analysis indicate that young people confer a certain relevance to religion on an internal and personal level, and that they attribute a historical value to it as a discipline. They also relate the versatility of religion to changing processes regarding beliefs and belonging to a religious community. Therefore, dialogue becomes the key tool for social cohesion in multicultural societies beyond mere tolerance, creating spaces for mutual transformation and generating a symmetrical relationship between the "Self" and the "Other".